ANALISIS KEBIJAKAN BAURAN PEMASARAN PADA PD MAHA JAYA TEKNIK PONTIANAK - B31108032, Dody Penarosa (Jurnal Manajemen Update, 2012)
Competition in the corporate world are increasingly stringent, in which case the company should have the initiative to be able to retain and win customers. Innovation is a very important factor and in addition to the integration of elements - elements of marketing mix or marketing mix of product innovation the company plays a role in determining the elements - elements such as the Marketing Mix: Product, price, promotion, and place, is a factor - a factor that can influence and encourage a consumer to purchase goods on offer. The purpose of this study was to determine the marketing mix policies implemented by the PD. Maha Jaya Teknik in Pontianak. The method used is descriptive method / qualitative using a questionnaire, which collected data are grouped according to predetermined criteria, and presented add up, then analyzed and conclusions drawn. Sample of 50 respondents of this study aims to describe the nature of something that is taking place at the time the research was done and examine the causes of a particular symptom. The results of this study indicate that the policy of the product is good quality product, and products that exist in PD Maha Jaya Teknik is complete and its functions in accordance with the wishes of the brands, types, and sizes and variations of existing products in the PD Maha Jaya Teknik in Pontianak in general is good. So in general it can be concluded that the existing products in the PD Maha Jaya Teknik in the Pontianak is good. Price policy is a major factor in making a purchase, the price set by the PD Maha Jaya Teknik in Pontianak is a factor that affects consumers in shopping. For pricing set by the PD Maha Jaya Teknik in Pontianak is moderate / low and the discount is always given to the consumer at the time he made a purchase in large quantities. On promotion, the promotional activities undertaken by PD Maha Jaya Teknik in Pontianak, the respondents generally get the products sold by the company through family / friends and the best promotions to attract consumers are price cuts. In terms of promotion, the role of relationships that have been bought also greatly affect the purchase and promotion policy according to the respondents who used the products in the PD Maha Jaya Teknik in Pontianak is word of mouth promotion, relationships, and through salespeople or marketers. Policies Place, location or the location of PD Maha Jaya Teknik in Mahakam street is located in a strategic and easy to find and with the ever-present availability of products to meet customer needs. With the easiness it is expected that customers had no difficulty in ordering the product. Keywords: Marketing Mix (Product, Price, Promotion, Place)